DATA PANEL ANALISIS : FAKTOR INTERNAL PERUSAHAAN DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN - Lilis Renfiana; Yudhisthira Ardana (Jurnal Internasional Ekonomi Islam, 2021)
This research aims to systematically, actual, and accurately explain the facts and characteristics of the company and their effect on financial performance. Data in the form of time-series data from 2015-2019 and cross-section data collected from the financial statements of automotive companies listed on the Indonesia Stock Exchange then obtained nine companies that meet the criteria. The independent variables are Firm Size, Leverage, Liquidity, and the dependent variable is financial performance as proxied by Return On Equity (ROA). The research used panel data techniques; Common Effect Model, Fixed Effect Model, and Random Effect Model. The results show that Firm Size partially has a negative and significant effect, meaning that the greater the assets owned by the company, the more complex the agency problems faced. The partial leverage variable has a negative and significant effect, means that the use of relatively high debt will cause fixed costs in the form of interest expenses and loan principal installments to be paid, the greater the fixed costs. The liquidity variable partially has a positive and insignificant effect. This means that changes that occur in both the number of current assets or current liabilities affect increasing profits so that the increase in Liquidity (CR) or the level of liquidity affects changes in increasing company performance (ROA).